THE INFLUENCE OF SUPPLIER TRUST AND SUPPLIER COMMITMENT TO SUPPLIER PERFORMANCE THROUGH INFORMATION SHARING AND COLLABORATION - Warniancy Ariesty (Jurnal Manajemen dan Kewirausahaan, 2016)
This research will discuss obstacles in producing the optimal number of nickel, this is related to the performance of the supplier. The object of this research is PT. Vale Indonesia Tbk. supplier companies incorporated the law of PT and CV, as well as the minimum of two years has become an active supplier. The purpose of this research is to test and analyze all variables that affect the supplier performance, such as supplier trust, supplier commitment, information sharing and collaboration. The research method used is SEM (Structural Equation Modeling) based on GeSCA (General Structured Component Analysis). The result from the research obtained that supplier commitment variable affect supplier performance through information sharing and collaboration, while the variable of supplier trust has no effect to measure supplier performance.